2016
DOI: 10.1016/j.jasrep.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sources: The pXRF analysis of obsidian from Kenan Tepe, S.E. Turkey

Abstract: Obsidian is often seen as a proxy for exchange and networking even though the relationship between these elements can be somewhat indirect. Nevertheless, recent studies which involve the provenance analysis of a large number of artefacts from a single site have opened up a number of avenues which are simply not visible when only a small number of artefacts can be provenanced. In this paper, after evaluating the efficacy of our pXRF protocol for the provenancing of large numbers of obsidian artefacts, we go on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…The analyses of large data sets in the Manchester Obsidian Laboratory is ongoing or in course of publication and the results that we use here are preliminary. Here we draw on the analysis of 675 artefacts from Umm Dabaghiyah, 509 artefacts from Jericho, and 432 artefacts from Domuztepe (the most recent summary of which is in Frahm et al, 2016) as well as 822 artefacts from Kenan Tepe (Campbell and Healey, 2016). These analyses were undertaken using a portable Niton XL3t980…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses of large data sets in the Manchester Obsidian Laboratory is ongoing or in course of publication and the results that we use here are preliminary. Here we draw on the analysis of 675 artefacts from Umm Dabaghiyah, 509 artefacts from Jericho, and 432 artefacts from Domuztepe (the most recent summary of which is in Frahm et al, 2016) as well as 822 artefacts from Kenan Tepe (Campbell and Healey, 2016). These analyses were undertaken using a portable Niton XL3t980…”
Section: Methodsmentioning
confidence: 99%
“…At Pre-Pottery Neolithic A (PPNA) Körtik Tepe in the Upper Tigris region, the larger sample size demonstrated that obsidian from Bingöl B was acquired in a different form to that from other sources, although once at site all were treated similarly (Carter et al, 2013). At Kenan Tepe, Group 3d obsidian appears to have been acquired in a raw state and worked using different techniques from the other obsidians present, as well as with a nuanced pattern of change over relatively short periods of time (Campbell and Healey, 2016).…”
Section: The Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument generates X‐rays via a miniaturized 50 kV, 200 μA tube with a silver anode. The procedures used in this analysis have been published by Campbell and Healey (). A 90‐s reading time was used, composed of 20 s each using the main, low and high filters and 30 s using the light filter.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some southern Caucasian obsidian has recently been identified at sites in south‐eastern Turkey and north‐western Iran, but only after the later part of the Pottery Neolithic period (Glascock ; Nadooshan et al . ; Campbell and Healey ; Frahm et al . ; Mouralis et al .…”
Section: Introductionmentioning
confidence: 99%